Optimizing Problem-Solving Competencies Through Inquiry-Based Learning and Gamified Formative Assessment in Primary Mathematics - Koswara, Ajeng Fatimah Putri; Rusnilawati, Rusnilawati (Profesi Pendidikan Dasar, 2024)
Nusukan Primary School primarily utilises conventional teaching methods, with limited incorporation of technology. The objective of this study was to evaluate the efficacy of the Kahoot-supported Inquiry-Based Learning model in enhancing the problem-solving skills of primary school students. Employing a quantitative approach with a quasi-experimental design, the research was conducted with two third-year classes at Nusukan Primary School. The experimental group received instruction through the Inquiry-Based Learning model integrated with Kahoot media, while the control group was taught using conventional methods supplemented by PowerPoint presentations. Data were collected via pre- and post-intervention problem-solving assessments to measure the comparative effectiveness of the instructional approaches. The findings of this study indicate that the experimental group, which received instruction through the Kahoot-supported Inquiry-Based Learning model, demonstrated significantly superior problem-solving abilities compared to the control group. The experimental group achieved an N-Gain score of 78%, classified as 'effective,' whereas the control group recorded a score of 38%, deemed 'less effective.' Furthermore, the integration of Kahoot media enhanced the efficacy of the Inquiry-Based Learning approach, particularly during the second phase (organising students) and the concluding phase. This enhancement contributed substantially to the improvement of problem-solving skills among primary school students.